Perceptions of teachers and experts regarding school gardening practices to enhance agriculture and food literacy among school children - Indramali, O.S.; Karunanayaka, M.M.S.; Perera, T.; Dissanayake, U.; Kudagammana, T.; Mohotti, A. J.; Hunter, Danny; Silva, K.D.R.R. (2025)
Presented at the Annual Scientific Sessions of the Nutrition Society of Sri Lanka,18th and 19th of January 2025, Colombo, Sri Lanka. School garden provides opportunities for shaping children's food choices through hands-on learning that promotes healthy eating habits. This qualitative study aimed to identify current agronomic practices, explore challenges in school gardening and suggest improvements for a model garden to enhance students' knowledge, and attitudes toward agriculture, and nutrition. The present study involved in-depth interviews with 10 agriculture teachers from 18 schools across two districts (Kurunegala and Gampaha) in Sri Lanka, and 10 agriculture experts. Information on agronomic practices, challenges in school gardening, and best strategies for implementing model garden to positively impact students' knowledge, attitudes toward agriculture, and nutrition were gathered through interviews.